Porous superstructure with excellent liquid absorption performance and additive manufacturing method

By designing a porous superstructure in the liquid absorbent core, combining additive manufacturing and transition layer printing technology, the problem of insufficient permeability and capillary force of the liquid absorbent core is solved, and the liquid absorbent performance and heat transfer performance are improved, adapting to complex shapes manufacturing needs.

CN119164229APending Publication Date: 2024-12-20SICHUAN NINGYI TECH CO LTD

Patent Information

Application Number
CN202410368681.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-03-28
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The penetration rate of the existing liquid absorbing core is not high, and the capillary force of the lattice liquid absorbing core is insufficient, resulting in damage to heat transfer performance. It is difficult for traditional manufacturing methods to prepare porous liquid absorbing structures with high connectivity and complex shapes, which increases the cost and difficulty. .

Method used

Using porous superstructures, including macroscopic point matrix structures and microscopic pores, are prepared by additive manufacturing technology, using macroscopic pores to provide high permeability and microscopic pores to provide high capillary force, combined with transition layer printing technology to improve liquid absorption performance and heat transfer performance.

Benefits of technology

The liquid absorption and heat transfer performance of the liquid absorption core are significantly improved, the permeability and capillary force are comprehensively optimized, the mechanical strength and functional performance of the structure can be regulated, the preparation cost is reduced, and the manufacturing needs of complex shapes are adapted.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to the technical field of liquid absorption cores, and discloses a porous superstructure with excellent liquid absorption performance, which comprises a macroscopic lattice structure, the macroscopic lattice structure is manufactured by using an additive manufacturing method, the macroscopic lattice structure forms a macroscopic porous structure with lattice arrangement, the macroscopic porous structure is in a millimeter level, and the macroscopic porous structure is a porous structure. The lattice pillars of the macroscopic lattice structure form a micro porous structure, the micro porous structure is micron-sized, the diameter of macroscopic pores in the macroscopic porous structure is 200-1000 microns, and the diameter of micro pores in the micro porous structure is 50-150 microns. The macroscopic pores provide good permeability, and the microscopic pores of the porous material provide good capillary force, so that comprehensive optimization of the permeability and the capillary force is achieved through cooperation of the macroscopic pores and the microscopic pores, and the liquid absorption performance and the heat transfer performance of the liquid absorption core are greatly improved; and meanwhile, the macroscopic / microcosmic pore proportion, lattice configuration and distribution can be adjusted to realize regulation and control of liquid absorption performance and mechanical strength, and the integrally-formed liquid absorption core with the structure and the function integrated is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of liquid absorbent cores, and in particular to a porous superstructure with excellent liquid absorbent performance and an additive manufacturing method. Background Art

[0002] As a high heat transfer performance component, the heat pipe utilizes the principle of heat conduction and the rapid heat transfer properties of phase change medium. It quickly transfers the heat of the heating object to the outside of the heat source through the heat pipe. Its thermal conductivity exceeds that of any known metal. Generally, a heat pipe consists of a tube shell, a liquid wick and an end cap. The inside of the heat pipe is pumped into a negative pressure state and filled with a suitable liquid. This liquid has a low boiling point and is easy to volatilize. The tube wall has a liquid wick, which is made of capillary porous material. One end of the heat pipe is the evaporation end, and the other end is the condensation end. When one end of the heat pipe is heated, the liquid in the capillary tube quickly vaporizes, and the vapor flows to the other end under the power of heat diffusion, and condenses at the cold end to release heat. The liquid then flows back to the evaporation end along the porous material by capillary action, and conducts continuously in this way until the temperature at both ends of the heat pipe is equal. At present, heat pipe radiators have been widely used in the fields of aviation weather, electronic equipment, electric vehicles, etc.

[0003] The key component of the heat pipe is the liquid wick structure, which can transfer liquid without external power through its own capillary action. Excellent liquid absorption performance (capillary performance) requires a smaller effective pore size Reff to provide a larger capillary force, and at the same time has a high permeability K, expressed as K / Reff. Traditional liquid absorption cores are made by wire mesh or powder metallurgy. However, due to its own characteristics, the wire mesh will warp and break after repeated use. At the same time, the stacking of multiple layers of wire mesh will cause inter-mesh bonding, reducing the liquid absorption capacity of the structure. Powder metallurgy makes it difficult to prepare fluid channels such as heat pipe grooves and through holes with high connectivity and complex shapes, which hinders the full circulation of the working fluid and reduces the maximum heat transfer capacity of the heat pipe. At the same time, the pore size of the porous liquid-absorbing structure prepared by the powder metallurgy method is uncertain. Under the action of gravity, the liquid working fluid is very likely to be unable to reach the evaporation section to participate in the circulation due to insufficient capillary force provided by the pores, which eventually causes the evaporation section to dry up and the heat pipe to fail. Secondly, the porosity of the inner, middle and outer three-layer lattice structure of the existing liquid-absorbing core design gradually decreases, that is, the pore size gradually increases and the capillary force gradually decreases. Therefore, when the heat pipe is working, the outer lattice structure (2mm×2mm×2mm) cannot provide enough capillary force to transmit the liquid working fluid, which impairs the heat transfer performance of the structure. In addition, the maximum size of the pore design of the inner lattice structure is 0.001-0.2mm. It is difficult to maintain sufficient dimensional accuracy when preparing the lattice structure using general additive manufacturing technology. Generally, the pores are completely blocked. Only fine printing technology can be used, which will greatly increase the cost of structural preparation and is difficult to promote and apply on a large scale. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a porous superstructure with excellent liquid absorption performance and an additive manufacturing method, which are used to solve the technical problems of low permeability of porous liquid absorbent cores and insufficient capillary force of lattice liquid absorbent cores.

[0005] The objective of the present invention is achieved through the following technical scheme: a porous superstructure with excellent liquid absorption performance, comprising a macroscopic lattice structure, wherein the macroscopic lattice structure forms a macroscopic porous structure with a lattice arrangement, wherein the macroscopic porous structure is at the millimeter level, and the lattice pillars of the macroscopic lattice structure form a microscopic porous structure, wherein the microscopic porous structure is at the micron level, wherein the macroscopic pore diameter in the macroscopic porous structure is 200-1000 microns, and the microscopic pore diameter in the microscopic porous structure is 50-150 microns.

[0006] In some embodiments, the macroscopic pores and microscopic pores are distributed uniformly or in a gradient manner in the height direction of the macroscopic lattice structure.

[0007] In some embodiments, the macroscopic pores and microscopic pores are distributed uniformly or in a gradient manner in the radial direction of the macroscopic lattice structure.

[0008] In some embodiments, the macroscopic porous structure is composed of one or more combinations of through holes, simple cubic, body-centered cubic, face-centered cubic, simple hexagonal, simple tetragonal, body-centered tetragonal, hexagonal, simple orthogonal, orthogonal, body-centered orthogonal, face-centered orthogonal, simple oblique deformation body and TPMS.

[0009] A porous superstructure additive manufacturing method is used to manufacture the above-mentioned porous superstructure, comprising the following steps:

[0010] S1. Design a structural model that meets the shape of application requirements in the modeling software;

[0011] S2. Using additive manufacturing technology, the powder is melted and stacked layer by layer to form the required design model, and appropriate printing parameters are selected to produce microscopic pores in the lattice pillars of the design model;

[0012] S3. After fabrication is completed, the structure is cut off from the substrate.

[0013] In some embodiments, in step S2, a transition layer is printed; a transition layer with a porosity of about 20% is prepared between the porous superstructure and the substrate, so that the porous superstructure and the substrate can be tightly combined, heat is quickly transferred, and thermal stress is reduced.

[0014] In some embodiments, the transition layer printing parameters are P-150W, V-1200mm / s, H-120um, and the layer thickness is 30um.

[0015] The beneficial effects of the present invention are:

[0016] 1. The macroscopic pores provide good permeability, and the microscopic pores of the porous material provide good capillary force. The combination of the two achieves the comprehensive optimization of permeability and capillary force, greatly improving the liquid absorption performance and heat transfer performance of the absorbent core. At the same time, the macroscopic / microscopic pore ratio, lattice configuration and distribution can be adjusted to achieve the regulation of liquid absorption performance and mechanical strength, and prepare an integrated structural and functional absorbent core.

[0017] 2. The porous superstructure is manufactured by additive manufacturing, making full use of the flexibility of additive manufacturing. The cross-section of the liquid-absorbing structure can be prepared into any shape to meet various working conditions.

[0018] 3. Compared with the traditional manufacturing method, a transition layer printing method is proposed to prepare a transition layer with a porosity of about 20% between the superstructure wick and the substrate, so that the porous wick and the substrate can be tightly combined, heat transfer is fast, and thermal stress is reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 A schematic diagram of the structure of a porous superstructure with excellent liquid absorption performance according to the present invention;

[0020] Figure 2 A schematic diagram of the distribution of macroscopic pores in a porous superstructure with excellent liquid absorption performance according to the present invention;

[0021] Figure 3 A schematic diagram of the distribution density of macroscopic pores in a porous superstructure with excellent liquid absorption performance according to the present invention;

[0022] Figure 4 Schematic diagram of the types of lattice structures filled inside the wick;

[0023] Figure 5 Schematic diagram of the comparison between sample permeability and effective pore radius;

[0024] Figure 6 This is a comparison chart of the capillary performance coefficient of the samples;

[0025] Figure 7 is the liquid absorption curve of the sample porous superstructure;

[0026] Figure 8 Schematic diagram of the liquid absorption performance results of the sample porous superstructure;

[0027] Fig. 9 This is a schematic structural diagram of Example 1 of a porous superstructure with excellent liquid absorption performance of the present invention;

[0028] Fig.10 The liquid absorption curve and capillary performance schematic diagram of the porous superstructure of Example 1;

[0029] Fig.11 This is a schematic structural diagram of Example 2 of a porous superstructure with excellent liquid absorption performance of the present invention;

[0030] Fig.12 It is a schematic diagram of the liquid absorption curve and capillary performance of the porous superstructure of Example 2;

[0031] Fig.13 The liquid absorption curve and capillary performance schematic diagram of the porous superstructure of Example 3;

[0032] In the figure, 1-macroscopic lattice structure, 2-macroscopic porous structure, 3-microscopic porous structure. DETAILED DESCRIPTION

[0033] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings, but the protection scope of the present invention is not limited to the following.

[0034] like Figures 1 to 4 As shown, a porous superstructure with excellent liquid absorption performance includes a macroscopic lattice structure 1, the macroscopic lattice structure 1 forms a macroscopic porous structure 2 with a lattice arrangement, the macroscopic porous structure 2 is of millimeter level, the lattice pillars of the macroscopic lattice structure 1 form a microscopic porous structure 3, the microscopic porous structure is controlled by the preparation process to be made into a random porous structure, the microscopic porous structure 3 is of micron level, the macroscopic pore diameter in the macroscopic porous structure 2 is 200-1000 microns, the microscopic pore diameter in the microscopic porous structure 3 is 50-150 microns, the macroscopic pores of the macroscopic lattice structure 1 provide good permeability, and the microscopic pores of the porous material provide good capillary force, and the two cooperate to achieve a comprehensive optimization of permeability and capillary force, greatly improving the liquid absorption performance and heat transfer performance of the liquid absorbent core; at the same time, the macro / micro pore ratio, lattice configuration and distribution can be adjusted to achieve liquid absorption performance and mechanical strength regulation, and an integrally formed liquid absorbent core with integrated structure and function is prepared.

[0035] Preferably, Figure 1 and Figure 2 As shown, the macroscopic pores and microscopic pores are evenly or gradiently distributed in the height direction of the macroscopic lattice structure 1. For example, for a wick that transfers mass in the height direction, a smaller capillary force is required to counteract gravity in the lower part of the wick. Therefore, the proportion of microscopic pores for capillary action can be reduced, and the proportion of macroscopic pores can be increased to improve permeability. In the higher part of the wick, a larger capillary force is required to counteract gravity. Therefore, the proportion of microscopic pores can be increased to increase capillary action.

[0036] Preferably, Figure 1 and Figure 3As shown, the macroscopic pores and microscopic pores are evenly or gradiently distributed in the radial direction of the macroscopic lattice structure 1. For the absorbent core that transfers mass in the radial direction, the ratio of macroscopic pores to microscopic pores can be adjusted in the radial direction to achieve comprehensive optimization of capillary action and permeability. In specific implementation, the microscopic pores in one direction can be prepared by one or more additive processes.

[0037] Furthermore, if Figure 1 and Figure 4 As shown, the macroscopic porous structure 2 is composed of one or more combinations of through holes, simple cubic, body-centered cubic, face-centered cubic, simple hexagonal, simple tetragonal, body-centered tetragon, centered hexagonal, simple orthogonal, centered orthogonal, body-centered orthogonal, face-centered orthogonal, simple oblique and their deformed bodies and TPMS, and the inside of the wick is filled with a plurality of macroscopic porous structures 2, and the filling lattice cells adopt the above-mentioned shape structure but are not limited to the above-mentioned shape structure, among which the simple cubic hole provides the highest permeability; the body-centered cubic provides strong mechanical strength; the three-periodic minimal surface TPMS has the largest specific surface area and the best heat transfer characteristics.

[0038] A porous superstructure additive manufacturing method comprises the following steps:

[0039] S1. Design a structural model that meets the shape of application requirements in the modeling software;

[0040] S2. Using additive manufacturing technology, the powder is melted and stacked layer by layer to form the required design model, and appropriate printing parameters are selected to produce microscopic pores in the lattice pillars of the design model;

[0041] S3. After fabrication is completed, the structure is cut off from the substrate.

[0042] However, in the actual preparation process, since the porosity of the porous structure is as high as 50% or more, its formability is greatly affected by thermal stress. Therefore, transition layer printing is used in step S2; a transition layer with a porosity of about 20% is prepared between the porous superstructure and the substrate, so that the porous superstructure and the substrate can be tightly combined, heat transfer is fast, and thermal stress is reduced. The printing parameters of the transition layer are P-150W, V-1200mm / s, H-120um, and the layer thickness is 30um. In addition, the microscopic pores are regulated by process parameters. Therefore, the sample can be arbitrarily adjusted according to the spatial shape of the use environment. The maximum size of the sample is only affected by the additive machine. This process can be applied to samples of any size.

[0043] like Figure 4As shown, the above structural design, the structural type can be selected from through-hole, lattice, TPMS, cubic, hexagonal and other structures. The high permeability of the lattice structure can provide high permeability, and the large specific surface area of ​​the TPMs structure can provide a high heat exchange area to improve the heat exchange efficiency. At the same time, in order to meet different working conditions, the conversion of extremely high permeability and extremely high capillary force can be achieved by adjusting the number and distribution of holes (the ratio of microscopic pores to macroscopic pores); the macroscopic pore diameter is 200-1000 microns, the pillar diameter is 200-600 microns, the powder material used is 316L, the powder diameter is 15-53 microns, and other powders can also be selected, such as titanium alloy powder, aluminum alloy powder, etc.

[0044] In summary, the problem of additive manufacturing of porous or lattice absorbent structures has been solved, greatly improving the capillary performance and heat transfer performance of the absorbent structure. By adjusting the additive process parameters, the absorbent core structure is prepared into a composite porous structure, the macroscopic pores provide high permeability, and the microscopic pores provide high capillary force. The macroscopic and microscopic porous composite structure solves the contradiction that the capillary force and permeability of the traditional structure are difficult to improve at the same time, thereby achieving a balance between the structural permeability and the capillary force, and greatly improving the capillary performance and heat transfer efficiency of the absorbent core structure. Figure 5 As shown, the composite porous structure proposed in this patent has a significantly improved permeability K compared to a single lattice or a single porous structure, and the effective pore radius Reff is larger than that of the porous sample and slightly smaller than that of the lattice sample. Figure 6 As shown in the figure, the composite porous structure can obtain better comprehensive capillary performance K / Reff. Compared with a single porous or lattice structure, the capillary coefficient is increased by about 300%. Secondly, the composite porous structure has a large degree of freedom in regulating the liquid absorption performance. According to the actual application conditions and the characteristics of the heat transfer medium, the lattice structure design and porous material design can be freely adjusted to adjust the optimal capillary force and permeability to achieve the optimization of the structural liquid absorption performance; additive manufacturing can form complex liquid absorption core structures; reduce welding and other processes, shorten the cycle; improve the surface roughness to greatly improve the capillary force of the structure; one-piece molding reduces the number of heat transfer interfaces, and the heat transfer efficiency will be greatly improved.

[0045] In order to characterize the performance of the structure, the capillary rise method was used for testing:

[0046] The following table shows the printing parameters of each sample.

[0047] serial number Power W Scanning speed mm / s Scanning distance um Layer thickness Spot diameter um Energy density J / mm3 1 100 1600 130 60 30 8.01 2 100 1200 150 60 30 9.26 3 100 1400 90 60 30 13.23 4 200 1400 150 60 30 15.87 5 200 1600 90 60 30 23.15

[0048] According to the above printing parameters, we can get Figure 7 The sample absorption curve shown in the figure can be fitted with the MT model to obtain the absorption performance parameters of the structure. The fitting formula is as follows:

[0049]

[0050]

[0051] In the equation, μ, σ, ρ are the viscosity, surface tension and density of the fluid, ε, T, X are the porosity, thickness and width of the wick, W is the Lambert function, and the C parameter is a function of the fluid properties and the geometric shape of the wick. By calculating with the formula, the permeability K and the effective pore radius Reff of the structure are obtained, and finally the capillary performance coefficient K / Reff is obtained, such as Figure 8 As shown in the figure, the sample absorption performance results are shown in the figure; it can be seen that the composite porous absorption structure is integrated by laser selective melting additive manufacturing technology. By adjusting the printing parameters such as laser power, scanning speed and scanning spacing, porous pillars with different densities and pore sizes are prepared to achieve the preparation of a two-level composite porous lattice structure. At the same time, adjusting the additive manufacturing surface printing parameters can increase the surface roughness of the lattice, thereby improving the capillary force and absorption performance of the structure.

[0052] Embodiment 1: Fig. 9 and Fig.10 As shown, the porous superstructure sample model is determined, and the macroscopic porous structure 2 is determined by using Magics or Solidwork software. The primary macroscopic pores are square holes with a pore diameter of 600 microns and a spacing of 400 microns between the pores. The secondary microscopic pores are formed in the model entity by adjusting the additive manufacturing printing parameters. A lower energy density parameter is selected to make the powder incompletely melted, and irregular secondary pores are formed between the powders. The additive manufacturing method in this embodiment is laser selective melting technology (SLM), with a laser power of 100W, a scanning speed of 1600mm / s, a scanning spacing of 130 microns, a layer thickness of 60 microns, a spot diameter of 30 microns, a laser energy density of 8.01J / mm3, and a secondary pore size of 50-150 microns. After printing is completed, the sample is cut from the substrate, and then ultrasonic cleaning is used to remove the unmelted powder in the pores, which is a liquid absorption superstructure. The capillary rise method is used to characterize the liquid absorption performance, and the results are shown in the figure. Fig.10 Then, the liquid absorption curve was fitted using formula (1) to obtain the capillary performance parameters of the structure, with a permeability (K) of 1.0495×10-9m2, an effective pore radius (Reff) of 323μm, and a capillary performance coefficient (K / Reff) of 3.24×10-6m.

[0053] Embodiment 2: Fig.11 and Fig.12 As shown, compared with Example 1, this embodiment changes the primary macroscopic pore structure into a circular shape, and the secondary microscopic pore printing parameters are: laser power 100W, laser scanning speed 1200mm / s, laser scanning spacing 150μm, layer thickness 60μm, spot diameter 30μm, and secondary pores 50-125μm. (The parts not mentioned in this embodiment are the same as Example 1) The structure of the embodiment is as follows Fig.11 The structural liquid absorption curve and capillary performance parameters are shown in Fig.12 As shown, the structural permeability (K) is 6.86×10-10m2, the effective pore radius (Reff) is 337μm, and the capillary performance coefficient (K / Reff) is 2.03×10-6m.

[0054] Embodiment 3: Fig.13 As shown, compared with Example 1, this embodiment changes the secondary microscopic pore printing parameters, laser power 100W, laser scanning speed 1200mm / s, laser scanning spacing 150μm, layer thickness 60μm, spot diameter 30μm, secondary pore 50-125μm. (The parts not mentioned in this embodiment are the same as Example 1) The liquid absorption curve and capillary performance parameters of the structure of Example 3 are shown in Fig.13 As shown in the figure, the structural permeability (K) is 1.03×10-9m2, the effective pore radius (Reff) is 390μm, and the capillary performance coefficient (K / Reff) is 2.64×10-6m.

[0055] In the description of the present invention, it is necessary to understand that the terms "coaxial", "bottom", "one end", "top", "middle", "the other end", "upper", "one side", "top", "inside", "front", "center", "two ends" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention; and it is known to those skilled in the art that the beneficial effects to be achieved by the present invention are only to achieve better beneficial effects under specific circumstances compared with the current implementation schemes in the prior art, rather than to directly achieve the best use effect in the industry.

[0056] The above is only a preferred embodiment of the present invention. It should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art shall not deviate from the spirit and scope of the present invention, and shall be within the scope of protection of the claims attached to the present invention.

Claims

1. A porous superstructure with excellent liquid absorption performance, characterized in that: The invention comprises a macroscopic lattice structure (1), wherein the macroscopic lattice structure (1) forms a macroscopic porous structure (2) with a lattice arrangement, wherein the macroscopic porous structure (2) is of the millimeter order, and the lattice pillars of the macroscopic lattice structure (1) form a microscopic porous structure (3), wherein the microscopic porous structure (3) is of the micrometer order, wherein the macroscopic pores in the macroscopic porous structure (2) have a diameter of 200-1000 micrometers, and the microscopic pores in the microscopic porous structure (3) have a diameter of 50-150 micrometers.

2. A porous superstructure with excellent liquid absorption performance according to claim 1, characterized in that: The macroscopic pores and microscopic pores are distributed uniformly or in a gradient manner in the height direction of the macroscopic lattice structure (1).

3. A porous superstructure with excellent liquid absorption performance according to claim 2, characterized in that: The macroscopic pores and microscopic pores are distributed uniformly or in a gradient manner in the radial direction of the macroscopic lattice structure (1).

4. A porous superstructure with excellent liquid absorption performance according to claim 3, characterized in that: The macroscopic porous structure (2) is composed of one or more combinations of through holes, simple cubic, body-centered cubic, face-centered cubic, simple hexagonal, simple tetragonal, body-centered tetragonal, hexagonal, simple orthogonal, orthogonal, body-centered orthogonal, face-centered orthogonal, simple oblique deformation body and TPMS.

5. A method for additive manufacturing of a porous superstructure, for manufacturing the porous superstructure according to claim 4, characterized in that: The following steps are involved: S1. Design a structural model that meets the shape of application requirements in the modeling software; S2. Using additive manufacturing technology, the powder is melted and stacked layer by layer to form the required design model, and appropriate printing parameters are selected to produce microscopic pores in the lattice pillars of the design model; S3. After fabrication is completed, the structure is cut off from the substrate.

6. A method for additive manufacturing of porous superstructures according to claim 5, characterized in that: In step S2, a transition layer is printed; a transition layer with a porosity of about 20% is prepared between the porous superstructure and the substrate, so that the porous superstructure and the substrate can be tightly combined, heat is quickly transferred, and thermal stress is reduced.

7. A method for additive manufacturing of porous superstructures according to claim 6, characterized in that: The printing parameters of the transition layer are P-150W, V-1200mm / s, H-120um, and the layer thickness is 30um.

Citation Information

Patent Citations

  • Flexible ultrathin liquid absorption core with hierarchical porous structure, and manufacturing method thereof

    CN110267493A

  • Metal liquid absorption core with multi-aperture structure characteristic and manufacturing method thereof

    CN110385436A

  • Metal wick material with hierarchical pore structure and preparation method of metal wick material

    CN112872355A

  • Manufacturing method of composite porous structure wick

    CN114888304A

  • Porous capillary heat dissipation structure embedded with gradient holes and manufacturing method

    CN114916198A

Cited By

  • Porous suction filtration material as well as preparation method and application thereof

    CN119657922A

  • A porous suction filter material and its preparation method and application

    CN119657922B

  • Method for preparing gradient composite wick structure through fusion of laser powder bed

    CN119819941A

  • A method for preparing a gradient composite wick structure by laser powder bed fusion

    CN119819941B

  • Cross-scale porous structure and 3D printing forming method and device

    CN120228901A